If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 2 = (x + -5) Reorder the terms: 2 + 4x = (x + -5) Reorder the terms: 2 + 4x = (-5 + x) Remove parenthesis around (-5 + x) 2 + 4x = -5 + x Solving 2 + 4x = -5 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 2 + 4x + -1x = -5 + x + -1x Combine like terms: 4x + -1x = 3x 2 + 3x = -5 + x + -1x Combine like terms: x + -1x = 0 2 + 3x = -5 + 0 2 + 3x = -5 Add '-2' to each side of the equation. 2 + -2 + 3x = -5 + -2 Combine like terms: 2 + -2 = 0 0 + 3x = -5 + -2 3x = -5 + -2 Combine like terms: -5 + -2 = -7 3x = -7 Divide each side by '3'. x = -2.333333333 Simplifying x = -2.333333333
| 4y+2=3(y-5) | | 3(3+3x)=8(x-2) | | 3(3+3)=8(x-2) | | 6x/2-3 | | 7*7*7*7*7=212 | | 7*5=212 | | 3t-9=7-1 | | 6x+3y=15.75 | | 7z-5-5(z+1)=-(4z+7) | | 1/3*4x | | 2k^2+7k-30=0 | | 7-q/4=2.5 | | 7-4=2.5 | | -3x+10y=0 | | sx+ty=ufory | | 8v=-18 | | 4lnx+6=0 | | 7(x+2)-8(4+3x)=47 | | 7(x-2)-8(4+3x)=47 | | 9x^2-100x+1000=0 | | 4x-t=14 | | (9-3g)-(3+12g)= | | log(x-1)-log(x+1)-log(8)=-2 | | 2x-7y+z=-5 | | x^3+4x^2+60x-17=0 | | log(x-1)-2*log(x+1)-log(8)=-2 | | x+2x+2=2 | | -3=57+(n+1)-4 | | -3m(m-10)=0 | | 5x-7=3(x+3) | | -3x=40000 | | 5x-11=2(x+14) |